Remote monitoring and detection of water contamination in effluent treatment plants - Hossain, Akib; Das, Koushik; Galiba, Taskia; Abir, Mishkat (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2023.